Corporate social responsibility and financial statement comparability: Evidence from China. (28th January 2020) - Wang, Fangjun; Zhang, Zhichao; Xu, Luying
Abstract: This study examines the association between corporate social responsibility (CSR) performance and financial statement comparability. We use a sample of 7, 462 firm‐year observations from firms listed on China's stock exchanges from 2007 to 2016 and find that to some extent, firms with more positive CSR performance exhibit higher financial statement comparability, supporting the notion that managers have ethical concerns for stakeholder engagement. By contrast, firms with inferior adverse CSR performance exhibit significantly much lower financial statement comparability. Results are robust to alternative variable measurements and tests for endogeneity. Findings also suggest that CSR performance can be indicative of managerial opportunistic behaviours and the compliance incentive to follow accounting standards.